2020
DOI: 10.1590/s1678-3921.pab2020.v55.01609
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy logic applied to different adaptability and stability methods in common bean

Abstract: The objective of this work was to evaluate the efficiency of the methods of Eberhart & Russell and Lin & Binns, modified for the automation of decision-making by fuzzy logic, in assessing the adaptability and stability of common bean (Phaseolus vulgaris) cultivars. Eighteen cultivars of the “carioca” commercial group were evaluated in 11 environments, in Brazil. All results were obtained by programming in the R software. The developed controllers were based on the fuzzy inference system developed by Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(19 reference statements)
1
0
0
Order By: Relevance
“…However, they showed that a hybrid fuzzy controller of the Eberhart & Russell and Lin & Binns was useful and efficient to aid in the process of cultivar recommendation. Similar results on using fuzzy controllers to classify genotypes for grain yield were also found in common bean (Carneiro et al, 2018; Carneiro et al, 2020). These studies confirmed that the fuzzy hybrid controller of the two methods had the power to handle multiple parameters ( Pif, 0.25emPiu β0, β1 and R2) and appropriately link information from them to make proper conclusions regarding the behaviour of genotypes.…”
Section: Discussionsupporting
confidence: 68%
“…However, they showed that a hybrid fuzzy controller of the Eberhart & Russell and Lin & Binns was useful and efficient to aid in the process of cultivar recommendation. Similar results on using fuzzy controllers to classify genotypes for grain yield were also found in common bean (Carneiro et al, 2018; Carneiro et al, 2020). These studies confirmed that the fuzzy hybrid controller of the two methods had the power to handle multiple parameters ( Pif, 0.25emPiu β0, β1 and R2) and appropriately link information from them to make proper conclusions regarding the behaviour of genotypes.…”
Section: Discussionsupporting
confidence: 68%